Family Socioeconomic Factors as a Risk Factor for ARI Incidence in Toddlers in Pekauman Dalam Village, Banjar Regency, Indonesia - Dwiyanti, Ratih Dewi; Insana, Aima (Tropical Health and Medical Research, 2025)
Acute Respiratory Tract Infections (ARI) remain a leading cause of infant mortality worldwide, including in Indonesia. Banjar Regency, South Kalimantan, has the highest infant pneumonia mortality rate in the province, despite its lower prevalence. This situation necessitates a study of the risk factors contributing to the incidence of ARI, particularly from a family's socioeconomic perspective. This study aims to determine the relationship between the incidence of ARI in toddlers and family socioeconomic risk factors in Pekauman Dalam Village, Banjar Regency. This study used an analytical study design with a cross-sectional approach. A sample of 28 toddlers was selected using total sampling. Data were collected through structured questionnaires completed by the toddlers' mothers/caregivers. Data analysis was performed bivariately using simple binary logistic regression, with further analysis using the Chi-Square test and Fisher's Exact Test on significant variables. The results of the study showed that among the 28 toddlers examined, six toddlers (21.4%) exhibited symptoms of acute respiratory infections (ARI). Statistical analysis revealed that, among all variables tested, only the toddler's age had a significant association with ARI incidence (p = 0.001; Fisher's Exact Test = 0.011). Toddlers aged ?1 year had a higher proportion of ARI cases than toddlers aged >1 year. Other variables such as family income, home ownership, residential density, cooking fuel, and maternal education did not show statistically significant relationships, although some had p-values approaching the significance threshold. Toddler age was the main risk factor influencing ARI cases in this study. Although most other socioeconomic factors were not statistically significant, these aspects are still important to consider in ARI prevention efforts. This study can form the basis for more targeted preventive interventions in areas with high socioeconomic vulnerability.